2021
DOI: 10.2147/copd.s339340
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Clinical Utility of Various Chronic Obstructive Pulmonary Disease Case-Finding Tools

Abstract: Background and Aim Chronic obstructive pulmonary disease (COPD) is frequently underdiagnosed because of the unavailability of spirometers, especially in resource-limited outpatient settings. This study provides real-world evidence to identify optimal approaches for COPD case finding in outpatient settings. Methods This retrospective study enrolled individuals who were at risk of COPD (age ≥40 years, ≥10 pack-years, and ≥1 respiratory symptom). Eligible participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“… 6 Chen et al provided real-world evidence by comparing Spirobank Smart, a novel app-based spirometer, with the P COPD and COPD-PS. The results demonstrated that Spirobank Smart (AUC = 0.908) exhibited higher accuracy, sensitivity, and specificity than did the P COPD (AUC = 0.788) and COPD-PS (AUC = 0.726) in identifying those with COPD; 63 this finding is consistent with that of the meta-analysis. This study compares the discriminative accuracy of combination methods, including CATURE, and COLA in 3 low- and middle-income country settings (including Nepal, Peru, and Uganda).…”
Section: Comparison Of Case-finding Toolssupporting
confidence: 79%
“… 6 Chen et al provided real-world evidence by comparing Spirobank Smart, a novel app-based spirometer, with the P COPD and COPD-PS. The results demonstrated that Spirobank Smart (AUC = 0.908) exhibited higher accuracy, sensitivity, and specificity than did the P COPD (AUC = 0.788) and COPD-PS (AUC = 0.726) in identifying those with COPD; 63 this finding is consistent with that of the meta-analysis. This study compares the discriminative accuracy of combination methods, including CATURE, and COLA in 3 low- and middle-income country settings (including Nepal, Peru, and Uganda).…”
Section: Comparison Of Case-finding Toolssupporting
confidence: 79%
“…Emphysema slowly destroys the air sacs in the lungs, which interferes with the flow of air out while, bronchitis causes inflammation and narrowing of the bronchial tubes, which allows mucus to build up. Both conditions cause obstruction of airflow in the respiratory system and cause breathing problems (Chen et al, 2021). COPD patients will experience shortness of breath so that they experience an increase in external respiratory frequency (De Miguel-Díez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%